Opaque cells signal white cells to form biofilms in Candida albicans - Daniels, Karla J (2006)
Upon homozygosis from a/α to a/a or α/α, Candida albicans must still switch from the ‘white' to ‘opaque' phenotype to mate. It was, therefore, surprising to discover that pheromone selectively upregulated mating-associated genes in mating-incompetent white cells without causing G1 arrest or shmoo formation. White cells, like opaque cells, possess pheromone receptors, although their distribution and redistribution upon pheromone treatment differ between the two cell types. In speculating about the possible role of the white cell pheromone response, it is hypothesized that in overlapping white a/a and α/α populations in nature, rare opaque cells, through the release of pheromone, signal majority white cells of opposite mating type to form a biofilm that facilitates mating. In support of this hypothesis, it is demonstrated that pheromone induces cohesiveness between white cells, minority opaque cells increase two-fold the thickness of majority white cell biofilms, and majority white cell biofilms facilitate minority opaque cell chemotropism. These results reveal a novel form of communication between switch phenotypes, analogous to the inductive events during embryogenesis in higher eukaryotes.